Geospatial Information Literacy and Outreach in a GIS Environment. - Eva Dodsworth (Issues in Science and Technology Librarianship, 2008)
The author reflects on the need for librarians to promote geospatial information literacy and outreach in Geographical Information Systems (GIS) environment. She argues that geospatial information literacy combined with campus-wide outreach will help educate the faculty, staff and students on using GIS. She suggests that encouraging geospatial information literacy can be done through workshops, presentations and its inclusion in course content. She shares her own strategies on teaching students how to use GIS.